La admisibilidad del recurso de casación en la actualidad : perspectivas a la luz de la sanción del nuevo Código Procesal Penal de la Nación - Fusco, Leandro Ezequiel (2017)
The cassation appeal has suffered substantial modifications in its structure on the basis of decisions taken, specially by the National Supreme Court of Justice. That has entailed the need to restructure the criteria inside the Court of Cassation regarding the previously mentioned subject. This lecture aims to sketch and organize the Court?s jurisprudence, drawing general principles that can be utilized in the framework of criminal law praxis. Additionally, the nature of this appeal in the new national procedural code will be analyzed.